2014
DOI: 10.2174/0929866520666131119200255
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Thermostable p-nitrophenylphosphatase from Bacillus Stearothermophilus (Bs-TpNPPase)

Abstract: Thermostable p-nitrophenylphosphatase from Bacillus Stearothermophilus (Bs-TpNPPase) is involved in the Mg(2+)-dependent hydrolysis of the phosphoenzyme at an optimum reaction temperature of 55°C. Bs-TpNPPase has been cloned and overexpressed in the E.coli M15 strain. Based on the conserved active sites, the protein was suggested to be a member of the haloalkanoate dehalogenase (HAD) superfamily. Two site-specific point mutants of Bs-TpNPPase were prepared by changing the catalytic Asp10 and Thr43 to Ala10 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The yutF gene encodes a protein that was predicted to be involved in N-acetyl-glucosamine catabolism and similar to 4-nitrophenyl phosphatase [24]. The condition-dependent transcriptome analysis revealed that yutF was almost constitutively expressed at low levels [25].…”
Section: Resultsmentioning
confidence: 99%
“…The yutF gene encodes a protein that was predicted to be involved in N-acetyl-glucosamine catabolism and similar to 4-nitrophenyl phosphatase [24]. The condition-dependent transcriptome analysis revealed that yutF was almost constitutively expressed at low levels [25].…”
Section: Resultsmentioning
confidence: 99%
“…The reaction buffer contained 50 mM Tris-HCl pH 10.0, 1 mM MgCl 2 and 5 mM pNPP. Enzymes were incubated for 15 min at various temperatures ranging from 293 to 338 K. After the enzymes had been cooled on ice, their residual phosphatase activities were examined according to the method described by Guo et al (2013). Fitting of the collected data and calculation of T 1/2 were performed using GraphPad Prism 6.…”
Section: Thermostability Measurementsmentioning
confidence: 99%
“…The structure of wild-type TpNPPase (PDB entry 4kn8; Guo et al, 2013) was used as the search model. Refinement was carried out using PHENIX v.1.8.2-1309 (Terwilliger et al, 2009) and manual fitting of side chains was performed in Coot (Emsley & Cowtan, 2004).…”
Section: Structure Determinationmentioning
confidence: 99%
See 2 more Smart Citations